Uji Kinerja Surface Scanner 3D Menggunakan Sensor VL53L0X dan Mikrokontroler ATMEGA8535 - Maria, Putut Son; Susianti, Elva (Jurnal Teknik Elektro, 2019)
Digital data recording of the geometry of 3-dimensional objects require a 3D scanner tool which are mostly using an imagery sensor. However there is hardly used information of scanned result, named color. Imagery sensor requires high spesification processing unit as capable as a personal computer for data acquisition processing. This research aims to build a 3D surface scanner using a time of flight laser ranging sensor and to develop its simple function to become more valuable device. Using point to point displacement method, the sensor measures the distance between the outermost point of the object and the sensor surface perpendicularly, once when one measurement is done then the object to be rotated along with the rotary table. The prototype was built using the VL53L0X sensor and ATMEGA8535 microcontroller as a motor controller for rotary table and vertical axis. Scanned data is sent from the microcontroller to the computer to be visualized in real time. The results show that the VL53L0X sensor is suitable for scanning convex objects but it is not capable to handle objects with multiple cavities.